Determination of Human Serum Albumin with Tetra-amino Copper Phthalocyanine by Resonance Light Scattering Technique - Xue, Zhongjin; Zhang, Xuejun; Wang, Gao; Zhang, Dan; Zhou, Hanchang (Asian Journal of Chemistry, 2012)
Resonance light scattering has been extensively used in the detection of concentrations of biological macromolecules. For the development of resonance light scattering based protein detection sensor at the point-of-care, it is necessary to make the enhanced resonance light scattering wavelength move to long wave direction to improve the detection sensitivity. A method for determination of protein was developed in presence of tetra-amino copper phthalocyanine (TACuPc) by resonance light scattering technique. In acidic solution, the interaction between TACuPc and human serum albumin yielded strongly enhanced resonance light scattering signals at wavelength 454 nm and the enhanced intensity of resonance light scattering was proportional to the concentration of proteins. The effects of pH and interfering species on the determination of protein were examined. Under optimal conditions, the linear range of human serum albumin is 0-2 μg mL-1 and the detection limit is 19.37 ng mL-1.